Jerry Waldie Governor Campaign Fresno Headquarters - Watkins, Howard K. (1974)
?, ?, Jerry Roberts, ??, Jerry Waldie eating cake made by Anne Kipps in Waldie hat, back of Ruth Wall, Bob Llewellyn on far right